New Varieties and Perspective Genotypes of Hops - Nesvadba, Vladimír; Charvátová, Jitka; Štefanová, Lucie (KVASNY PRUMYSL, 2017)
Hop breeding in Czech Republic has been aimed at aroma and bitter hops for a long time. Recently, we have managed to get some new genotypes with a specifi c fl avour. In 2017 Gaia and Boomerang have been released. New genotypes 5193 and 5164 have been submitted to registration process. New generation of fl avour hops is typical by the wide variability of the various types of hop aroma.